SAT0128 Efficacy and safety of adalimumab treatment for refractory juvenile idiopathic arthritis-associated uveitis. (23rd January 2014) - Alekseeva, E.; Mitenko, E.; Bzarova, T.M.; Valiyeva, S.I.; Isayeva, K.B.; Chomakhidze, A.M.; Denisova, R.V.; Sleptsova, T.V.
Abstract : Background: The treatment of juvenile idiopathic arthritis (JIA)–associated uveitis is one of the serious problem of paediatric rheumatology, therefore development and implementation of new methods of treatment is relevant. Humanised anti-TNFα monoclonal antibody (adalimumab) is promising drug for the treatment of JIA-associated uveitis refractory to immunosuppressive drugs. Objectives: To evaluate clinical efficacy and safety of adalimumab therapy in patients with JIA-associated uveitis. Methods: 104 patients were enrolled in the study, 30 boys and 74 girls, 47 with poly-, 41 with oligoarthritis, 11 – with enthesitis related arthritis and 5 with sistemic onset JIA without systemic symptoms, 48 – with JIA-associated uveitis. Mean age of patients was 10 (range 3 – 17) years; mean of disease duration – 6, 7 (range 2 – 16) years. Before and during adalimumab therapy 104 patients have received methotrexate (range of dose 15-25 mg/m 2 /w), 38 patients – methotrexate in combination with cyclosporine (range of dose 4-4, 5 mg/kg/d), 54 children – oral glucocorticoids (range of dose 5-12 mg/kg/d), 48 patients with uveitis – topical corticosteroid drops, topical NSAID drops, 27 children – retrobulbar injections of steroids. Adalimumab was administrated by subcutaneous injection at dose 40 mg every 2 weeks during 1year. Adalimumab use was approved by the Local Ethics Committee. The efficacy of therapy was measured by ACR-pedi criteria. Changes in ocular inflammation were graded by M.J.Hogan's criteria. Results: The ACR-Pedi 30, 50, 70 were achieved 100%, 80%, 60% of patients at week 4 weeks, respectively. After 12 weeks of therapy 100%, 89% and 73% of patients achieved ACR-Pedi 30, 50 and 70 improvements rates, respectively. After 24 weeks of therapy ACR-Pedi 30, 50, 70 and 90 improvements rates was registrated in 100%, 91%, 74% of patients. The inactive disease was achieved by 56% of patient at week 24. The remission was achieved by 85% of patient at week 52. 89 of 96 eyes had redness before adalimumab therapy, 44 of 96 eyes – edema of iris, 38 of 96 – keratic precipitates, 29 of 96 – optic nerve edema, 20 of 96 – lens' inflamatory. After 8 weeks of adalimumab therapy remission of uveitis was reported in 62 of 96 eyes, 43 of 96 had keratic precipitates, 17 of 96- had lens' inflamatory. Improved visual acuity was noted in 63 of 96 affected eyes, active uveitis remained in 33 of 96 eyes. The dose of topical corticosteroid drops was decreased in 22 patients of 48, topical NSAID drops was discontinued completely in 24 patients of 48. Retrobulbar injections of steroids were stopped in all patients. Serious adverse events were not found. Conclusions: Thus, our results indicate that adalimumab is effective in children with JIA associated uveitis refractory to methotrexate, cyclosporine and corticosteroids. Disclosure of Interest: None Declared